Workshop Keterampilan Berbicara (Speaking): Membimbing Siswa SMA dalam Memahami dan Mengungkapkan Ide dengan Jelas - Asma Alhusna; Mona Afersa (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2023)
English speaking skills are an important aspect in developing high school students' communication skills. This workshop aims to improve high school students' speaking skills, especially in understanding and expressing ideas clearly. The workshop will cover a variety of communication strategies and techniques involving active interaction, group discussions, and hands-on exercises. Through a practical approach, workshop participants will be empowered to overcome common obstacles in speaking, including unclear expression of ideas, appropriate use of body language, and effective word choice. The expected result of this workshop is an increase in students' ability to compose and convey ideas in a structured and convincing manner. Apart from that, it is also hoped that there will be an increase in students' self-confidence in speaking in public. Thus, this workshop focuses not only on academic aspects, but also on developing interpersonal skills that are important for future success.